UV-Spectrophotometric Determination of Voriconazole in Bulk and Its Formulation - SRINU BABU, G.; A.I. RAJU, CH. (Asian Journal of Chemistry, 2010)
A simple, sensitive, spectrphotometric method in UV region has been developed for the determination of voriconazole in bulk and tablet dosage forms. Variconazole is a new antifungal drug, which shows maximum absorbance at 252 nm with apparent molar absorptivity of 5.28206 × 103 L/molcm. Beer’s law was obeyed in the concentration range of 5-80 μg/mL. Results of the analysis were validated statistically and by recovery studies.